Intellectual Property Protection and Financial Markets: Patenting versus Secrecy - Dass, Nishant; Nanda, Vikram; Park, Haemin Dennis; Xiao, Steven Chong (Review of Finance, 2021)
Abstract Firms rely on patenting and trade secrecy to protect their intellectual property. We study how changes in the trade-off between patenting and secrecy affect firms’ stock liquidity and financing outcomes. We show that an international trade agreement (TRIPS) that strengthened patent protection led to a 10.2% increase in patenting, accompanied by a 14.0%–27.1% improvement in stock liquidity for firms in patent-reliant industries. This in turn allows the affected firms to increase equity financing by 1.9% and reduce leverage by 5.9%. Our results suggest that policies that promote use of patenting over secrecy can reduce informational frictions in equity markets.